Effect of refrigeration, room temperature, and processing time on serum immunofluorescent antibody titers for Sarcocystis neurona - Claudia Valderrama‐Martinez; Andrea Packham; Shichen Zheng; Woutrina Smith; Magdalena Plancarte; Monica Aleman (Journal of Veterinary Internal Medicine)
Abstract Background Evaluating antibody titers for Sarcocystis neurona for the diagnosis of equine protozoal myeloencephalitis from serum samples is a common practice. However, ensuring timely and proper refrigeration is not always possible. Objectives To evaluate immunofluorescent antibody (IFA) titers for S. neurona from serum samples stored at room temperature and 4°C. Samples Twenty‐two serum samples. Methods Prospective longitudinal study. Two serum aliquots of 1 mL each were stored at room temperature (20‐23.3°C) and 4°C. The unrefrigerated aliquot was immediately tested for IFA titers. Both aliquots were retested on Days 5 and 10 after collection. A paired t test was used to compare IFA titers at different time points. Results There was no significant difference between IFA titers from baseline with those stored at room temperature at Days 5 (P = .741, 95% CI [−56.83, 78.65]), 10 (P = .677, 95% CI [−50.01, 75.46]), and between 5 and 10 days (P = 0.949, 95% CI [−57.50, 61.14]). There was no significant difference from baseline with those stored at 4°C for Days 5 (P = .964, 95% CI [−81.81, 85.45]), 10 (P = 0.573, 95% CI [−109.4, 62.15]), and between 5 and 10 days (P = .5, 95% CI [−102.6, 51.67]). There was no statistical difference between samples stored at room temperature and 4°C (P = .688, CI [−55.51, 37.33]) on Days 5 and 10 (P = .104, CI [−80.8, 8.07]). Conclusions and Clinical Importance Immunofluorescent antibody test titers for S. neurona are stable for up to 10 days at room temperature and 4°C.